The Integration of Classroom and Community Learning in Narrative Accounts of Co-Curricular Service - Anna Baker-Olson; Becca Folkes-Lallo; Elizabeth Thomas; Erin Walker; Hannah Luckes; Isabelle Blaber; Marsha Walton; Michele Becton (Michigan Journal of Community Service Learning)
Although we have evidence that reflection on community service enhances student development outcomes, we have little understanding of the process by which students integrate their academic and community experiences. This study is a part of a larger Participatory Research project, for which we collected 403 narrative accounts of awkward or meaningful experiences written by 123 Bonner Scholars. Members of an interpretive community which included Bonner Scholars examined a subset of these stories pertinent to students’ integration of classroom and community work. We reliably identified several ways in which students talked about course material in their descriptions of their community experiences. Students wrote frequently about applying skills or concepts that they learned in the classroom to their work in the community. In some instances, this integration led to expressions of cultural humility and critical analysis. In contrast, few authors discussed how their community-based learning contributed to the classroom. We identified obstacles to this, and we argue that the types of knowledge and knowledge production privileged in academia inhibits genuine collaboration with our students and colleagues across institutional divisions. We suggest ways in which we might better support integrative student learning, faculty development, and institutional improvement.